Ion-mediated conformational switches. Issue 3 (10th December 2014) - Knipe, Peter C.; Thompson, Sam; Hamilton, Andrew D.
Abstract : The ability to control the conformation of a single molecule in a reversible and stimulus dependent manner holds great promise for fields as disparate as drug delivery and molecular electronics. Here we offer a perspective on recent developments in ion-mediated switching architectures and their ability to perform in a range of settings. Abstract : Molecular switches are ubiquitous in Nature and provide the basis of many forms of transport and signalling. Single synthetic molecules that change conformation, and thus function, reversibly in a stimulus-dependent manner are of great interest not only to chemists but society in general; myriad applications exist in storage, display, sensing and medicine. Here we describe recent developments in the area of ion -mediated switching.